2019
DOI: 10.1101/802892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sphingosine 1-phosphate-regulated transcriptomes in heterogenous arterial and lymphatic endothelium of the aorta

Abstract: 26Despite the medical importance of G protein-coupled receptors (GPCRs), in vivo cellular 27 heterogeneity of GPCR signaling and downstream transcriptional responses are not understood. 28We report the comprehensive characterization of transcriptomes (bulk and single-cell) and 29 chromatin domains regulated by sphingosine 1-phosphate receptor-1 (S1PR1) in adult mouse 30 aortic endothelial cells. First, S1PR1 regulates NFkB and nuclear glucocorticoid receptor 31 pathways to suppress inflammation-related mRNAs. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…Critically, using scRNA-seq we identified novel GRNs in the early brain, such as SOX11, PLAG1, and E2F1, while also showing confirming our ATAC-seq and RNA-seq results which suggested that JUN, FOXF1, and FOXQ1 control maturation of the brain endothelium. Critically, AP-1 transcription factors, such as JUNB, control vascular development in the retina (Engelbrecht et al, 2020;Keisuke et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Critically, using scRNA-seq we identified novel GRNs in the early brain, such as SOX11, PLAG1, and E2F1, while also showing confirming our ATAC-seq and RNA-seq results which suggested that JUN, FOXF1, and FOXQ1 control maturation of the brain endothelium. Critically, AP-1 transcription factors, such as JUNB, control vascular development in the retina (Engelbrecht et al, 2020;Keisuke et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma S1P was extracted according to Engelbrecht et al 49 Briefly, plasma aliquots (5 or 10 µL) were first diluted to 100 mL with Tris-buffered saline (50 mmol/L Tris-HCl pH 7.5, 0.15 M NaCl). Extraction of S1P was done by adding 100 mL precipitation solution (20 nmol/L D7-S1P in methanol) followed by 30 s of vortexing.…”
Section: Methodsmentioning
confidence: 99%
“…For example, sphingosine-1-phosphate (S1P) is a potent bioactive lipid, which is mainly bound to HDL via apolipoprotein M (apoM) and albumin in the plasma 5 -7) . S1P, in the apoM/HDL-bound form, exhibits beneficial activities, such as anti-apoptotic 8) , anti-inflammatory 9) , vasoprotective [10][11][12][13] , insulin-stimulatory 14) , and mitochondriaprotective 15) activities, whereas S1P bound to albumin exerts harmful effects, such as the induction of PAI-1 16) , promotion of mesangial cell proliferation 17) , induction of vasoconstriction 18) , and induction of hepatic fibrosis 19,20) . Recently, we reported that the carrier proteins also influenced the physiological properties of other lipids; for example, albumin-associated lysophosphatidylinositol exerted proinflammatory effects on macrophages, whereas lipoprotein-associated lysophosphatidylinositol had only a minimal or no such proinflammatory effects 21) .…”
Section: Subjectsmentioning
confidence: 99%